MOTIVASI YANG BENAR DALAM PERTUMBUHAN DAN PENGEMBANGAN GEREJA MODERN: REFLEKSI 1 PETRUS 2:1 - Kezia Refina Prayogo; Samuel Herman (Phronesis: Jurnal Teologi dan Misi, 2024)
This research explores true motivation in the context of the growth and development of the modern church by detailing the role of Judas Iscariot as a case study. Through a qualitative and expositional approach, the author analyzes 1 Peter 2:1 to highlight the threats to true motivation and presents the story of Judas as a concrete illustration. The study emphasizes the urgency of maintaining the integrity of motivation in church ministry and provides insights into the risks and implications of incorrect motivation. Findings indicate that aligning motivation with Christian values is crucial to avoid potential risks and threats to church growth. This research details the concepts and implications of incorrect motivation, reminding church ministers to update strategies to address misguided motivations continually. Preserving the purity of heart and behavior is critical to ensuring true motivation in serving God and others.